Assessing the impact of community gardening on modifiable risk factors for non‑communicable diseases in urban populations - Abacan, Sheila Flores (My University, 2026)
This dissertation examines community gardening as a potential preventive strategy for non-communicable diseases among free-living adults in urban areas of the United States, using three methodologically distinct studies. The first study synthesizes existing research on urban community gardening in the United States. Across diverse study designs, the evidence shows that participation in community gardens is consistently associated with healthier dietary patterns, particularly increased vegetable intake, greater engagement in light to moderate physical activity, and improved psychosocial well-being. Gardening also serves as a restorative practice that reduces stress and strengthens social connections, although evidence for short-term changes in body weight remains mixed. The second study assesses physical health behaviors, health status, and non-communicable disease prevalence among adult community gardeners in urban Kansas. The findings indicate that gardeners have higher physical activity levels, lower obesity prevalence, and fewer chronic conditions compared to national averages. While favorable health outcomes were strongly influenced by sociodemographic factors such as age and education, moderate participation in community gardening emerged as a uniquely protective factor against non-communicable diseases. The third study explores the lived experiences of community gardeners in a small urban setting using a qualitative approach. Participants described how gardening evolved from a practical activity into a deeply meaningful lifestyle practice that supports healthy eating, routine physical movement, stress reduction, and social connection. Gardening was perceived not as formal exercise, but as functional movement integrated into daily life, particularly valued by older adults. Together, these studies demonstrate that community gardening supports multiple modifiable risk factors for non-communicable diseases by integrating nutrition, physical activity, and psychosocial well-being within urban living.
Keywords: Community garden; Non-communicable diseases; Urban agriculture; Urban health; Public health